Tubal Ligation, Marriage and Orders: Canons 1041 and 1055 - Hilliard, Marie T. (Roman Replies and CLSA Advisory Opinions 2015, 2015)
John Smith is a widower who married a widow, Mary, nine years ago. Together they have been attending classes to prepare him to be ordained a permanent deacon in the Catholic Church. During this time they have begun to appreciate the teachings of the Church on the sanctity of the conjugal act and the nature of marriage as being ordered to both the good of the spouses and the procreation and education of offspring. The couple has become aware of the grave and intrinsic evil of a ,:asectomy and a tubal ligation as mutilating and sterilizing procedures that violate bodily integrity and frustrate the natural ends of marriage. Both John and his wife have had such procedures after having had children and while in their prior marriages. John has been in spiritual direction and raises this issue with his director, only to be told that before he can be considered for ordination, he must have a dispensation from what can be considered an impediment to Holy Orders. John and Mary discuss this matter and wish to continue his pursuit of Holy Orders, but now Mary has concerns about the validity of the marriage, since the sterilizing procedures were done before they married. John questions whether their current marriage has even been consummated, based on the fact that he had a vasectomy prior to the marriage. They both question whether they are obligated to pursue surgical reversal procedures, especially since, while Mary is peri-menopausal, she potentially is fertile. They are directed to a canonist to resolve these concerns. Before doing so, they had both sought the Sacrament of Penance to be reconciled for having had these procedures.